Dark design [large type] - Mehl, Nancy (Mehl, Nancy. Erin Delaney mysteries, 2025)
"When Erin Delaney learns that a serial killer has mimicked the murder portrayed in her bestselling novel, her career as an author takes a detrimental turn. She joins her friend Kaely Quinn-Hunter, a former FBI profiler, to help identify a suspect, but the team is stumped, and Kaely fears for Erin's safety as they work to dismantle a web of fear and chaos. On top of tracking down a murderer, Erin must shoulder the weight of a haunted past and the claims that she stole the plot of her novel from one of her sources. But as the enemy looms closer than ever, Erin's life hangs in the balance."--